ANALISIS KONTRIBUSI PENDAPATAN PETANI PADI SAWAH DI KABUPATEN BARITO SELATAN - Lina Trisnawati; Betrixia Barbara; Trisna Anggreini (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2018)
This research aim to analysis knowing contribution of rice farming income to total income of farmer household of paddy rice in Regency of South Barito. The result is the percentage of the main income contribution is the work as a rubber farmer is the work that has the greatest contribution to the total income of households of rice farmers in South Barito regency of 78.88%. While the income of households from rice farming is the income that has the lowest contribution that is 8.12% to total household income, because in this regency majority of society's main job is to become rubber farmer, while for farmer farmer of paddy rice field, farmer only work it only subsistence does not give priority to increase household income.